Feeding preferences in aquatic invertebrates associated to Egeria densa in a tropical high-mountain lake - Pedroza-Ramos, Adriana (2020)
Introduction: The benthic fauna of the littoral zone in lakes is important in transferring energy to other trophic levels, habitat coupling, and helping to keep habitat stability. The study of this type of interactions in lentic systems is priority, since functional aspects about biological communities are unknown. Objective: Describing the trophic relations of aquatic invertebrates of the littoral zone in a tropical high mountain lake by characterizing gut content and stable isotope analysis of δ13C and δ15N. Methods: Samples of benthic invertebrates were collected in the littoral zone of the Lago de Tota where Egeria densa was present using a handheld net method. Samples were processed in the laboratory, organisms were identified, counted and weighed. Gut contents and δ13C and δ15N stable isotopes analysis were performed as well. Results: Records of the trophic relations of aquatic invertebrates, which live in the littoral in high mountain lentic ecosystem in the Neotropics are shown. The analysis of gut contents distinguished seven food items, microphytes and MOPF were the most frequent, and through the stable isotopes analysis (δ15N) we identified four trophic levels, among resources (macrophytes and POM), and consumers (detritivores, herbivores, and predators). The two upper trophic levels concentrated greater diversity and biomass. Conclusion: Most of the organisms studied were linked to omnivorous habits, evidenced in a wide spectrum of food items in their diet. The δ15N values show an enrichment, which occurs due to the effects of the tendency towards eutrophication of the system or due to unknown values of protozoa and bacteria that plays a fundamental role in the diet of these organisms, besides the δ13C values reported in organisms consumes, allows us to suggest an affinity with native resources of the littoral zone.